Learning Guidance to Improve Children's Numeracy Ability in Kelongkong Hamlet - Akpalia, Dayatun Fitri; Asmini, Tuti; Saputra, Dicki Wahyu; Elfridarian, Elfridarian; Melati, Pegi Prastika (Abdi Masyarakat, 2024)
Kelongkong Hamlet, which is located in Sambik Bangkol Village, is one of the Real Work Lecture (KKN) locations for STKIP Hamzar students. The results of observations of students in elementary and junior high schools in this village, especially in Kelongkong Hamlet, revealed that some children had low numeracy abilities. In this case, students focused their attention on elementary and junior high school age students in TPQ Dusun Kelongkong. One of the programs implemented to overcome this problem is tutoring, with the aim of increasing the numeracy skills of TPQ children in Kelongkong Hamlet. This guidance program includes providing numeracy material as well as simple practice questions which will be held from 01 August to 29 September 2024 every Monday to Wednesday, 16:00 – 17:30 WIT. From the results we observed, it shows that this program has succeeded in improving the numeracy skills of students at TPQ Dusun Kelongkong, as seen from their ability to solve the simple questions given.  Kata Kunci: Bimbingan Belajar, Numerasi